Medieval Europe from another angle. - Curta, Florin, author. Link
1 online resource.
Keywords: "While the Middle Ages represent a topic of perennial interest, most studies have addressed the western parts of the European continent, often from the angle of the written sources. This volume examines an area less known in the literary and archaeological evidence. The studies included therein provide significant insights into the history and archaeology of East Central and Eastern Europe during Late Antiquity and the early Middle Ages. This is the first volume of essays explicitly to reassess the significance of the region, as well as the role of the archaeological evidence in studying ethnicity in the Middle Ages, particularly in the case of the Slavs and the Avars. Because of its geographic, chronological, thematic, and methodological scope, this book offers a new perspective from a different angle on the analysis of the archaeological and written sources. Some chapters focus on settlement sites, others discuss artifacts from burial assemblages. As well as advancing new models for the analysis of the written sources in relation to ethnicity, Medieval Europe from Another Angle offers new approaches to the understanding of how ethnicity may have been constructed in the Middle Ages in material culture terms. It will appeal to scholars and students alike studying Late Antiquity and the early Middle Ages with an interest in material culture and its use in building ethnic boundaries"-- Provided by publisher.